Review of doctoral research on second language teaching and learning in Spain (2008–2010). (28th November 2012) - Serrano, Raquel; Miralpeix, Imma
Abstract : This paper reviews a selection of doctoral theses on language learning and teaching completed in Spain between 2008 and 2010. A total of 16 theses have been identified as representative – in terms of the topics under investigation and the methodology employed – of the doctoral research undertaken in Spain. Current topics include the development of speaking skills, motivation, learner autonomy, pragmatics, learning context, Content and Language Integrated Learning (CLIL), language learning by immigrant populations and, especially, classroom teaching. A variety of research methods were employed in the theses under review, and while most of them focus on adult learners, some also consider children. The interest of researchers in these topics is consistent with the challenges faced by language teachers in Spain, as well as with the new realities of teaching in this country, with its recently-arrived immigrant population, the expansion of CLIL programmes and the use of new technologies.